THE EFFECTIVENESS OF FIRE DISASTER MITIGATION TRAINING IN SURABAYA REGIONAL DISASTER MANAGEMENT AGENCY - Fierda Nurany; Heru Irianto; Fitria Virdaus Nuzula (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2024)
This study aims to analyze the effectiveness of the Surabaya City fire disaster mitigation training, the inhibiting and supporting factors in the fire disaster mitigation training and the efforts made by the Surabaya City BPBD in overcoming obstacles in the fire disaster mitigation training. The research method used is descriptive qualitative. Sources of information were determined using purposive sampling techniques, data collection techniques through library studies, interviews and documentation as well as data analysis techniques by data collection, data reduction, data display and drawing conclusions. The results of the study show that: (1) The effectiveness of fire disaster mitigation training at BPBD Kota Surabaya is categorized as quite effective. The results of the work which can be seen from the high level of community awareness, the duration of time adjusted to the scale of the participants present, the satisfaction of the community which can be seen from the satisfaction survey data, the adaptation of trainers in adjusting to environmental conditions during fire disaster mitigation training and the development carried out to improve effectiveness, namely through employee competency improvement programs or staff. (2) The inhibiting and supporting factors in the effectiveness of this training are the facilities and infrastructure factors, employee competency factors, applicable SOP factors and community participation factors. (3) Efforts made by BPBD Kota Surabaya are by carrying out competency certification, coaching and mentoring programs, attending routine training specifically for employees or staff and collaborating with other agencies.